2018
DOI: 10.3390/mi9020071
|View full text |Cite
|
Sign up to set email alerts
|

3D Printing Solutions for Microfluidic Chip-To-World Connections

Abstract: The connection of microfluidic devices to the outer world by tubes and wires is an underestimated issue. We present methods based on 3D printing to realize microfluidic chip holders with reliable fluidic and electric connections. The chip holders are constructed by microstereolithography, an additive manufacturing technique with sub-millimeter resolution. The fluidic sealing between the chip and holder is achieved by placing O-rings, partly integrated into the 3D-printed structure. The electric connection of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 43 publications
0
39
0
Order By: Relevance
“…To reduce leaching, Macdonald et al [ 13 ] experimented with coating SLA printed parts with wax and found that the coating was only effective at delaying the onset of toxicity (by ∼40 h). The authors of van den Driesche et al [ 118 ] removed the toxicity of parts printed by DLP in resins, E-Shell 300 and HTM140, by coating them in parylene-C, which is an ultra-thin biocompatible polymer coating. Coating parts with biocompatible hydrogels (e.g., PEG-DA) or PDMS may also be an effective strategy to remove toxicity of easily accessible photopolymeric resins.…”
Section: Methods For Mitigating Toxicity Of Polymeric Resinsmentioning
confidence: 99%
“…To reduce leaching, Macdonald et al [ 13 ] experimented with coating SLA printed parts with wax and found that the coating was only effective at delaying the onset of toxicity (by ∼40 h). The authors of van den Driesche et al [ 118 ] removed the toxicity of parts printed by DLP in resins, E-Shell 300 and HTM140, by coating them in parylene-C, which is an ultra-thin biocompatible polymer coating. Coating parts with biocompatible hydrogels (e.g., PEG-DA) or PDMS may also be an effective strategy to remove toxicity of easily accessible photopolymeric resins.…”
Section: Methods For Mitigating Toxicity Of Polymeric Resinsmentioning
confidence: 99%
“…40 µL), compatible with standard industrial pipetting robots. The mounting method for the bilayer chips is depicted in Figure 2a [3]. The chip is mounted in a chip slot located in a 3D printed holder (Part-1).…”
Section: Designing and Printing The Parallel Bilayer Analysis Platformmentioning
confidence: 99%
“…The laser ablation here specifically refers to a method of ablating and machining a micro flow channel on the surface of a polymer material by using a carbon dioxide laser with a wavelength of 10.6 µm [24].…”
Section: Laser Ablationmentioning
confidence: 99%